2008
DOI: 10.1097/aog.0b013e3181875b92
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Rate and Risk Factors for Fetal Loss After Chorionic Villus Sampling

Abstract: The estimated fetal loss rate after CVS was not significantly different from the group that had no procedure. Significant predictors of fetal loss after CVS were identified, but the accuracy of the final model for predicting fetal loss was only modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…26 At present, however, full molecular karyotyping is only available in the context of diagnostic testing, which has been shown to be safer than previously thought. [27][28][29][30] Some authors have suggested that adopting cfDNA testing as a second-tier investigation following a high-risk combined first trimester screen would miss only a very small proportion of chromosomal anomalies, 31 whereas others indicate that up to 16.9% of aneuploidy would be missed, even when diagnostic testing is limited to G-banded karyotyping. 32 Studies that have utilised molecular karyotyping indicate that standard cfDNA testing alone would not identify up to 23.4% of potentially clinically significant karyotypic abnormalities that would otherwise have been identified by combined first trimester screening and invasive testing.…”
Section: Discussionmentioning
confidence: 99%
“…26 At present, however, full molecular karyotyping is only available in the context of diagnostic testing, which has been shown to be safer than previously thought. [27][28][29][30] Some authors have suggested that adopting cfDNA testing as a second-tier investigation following a high-risk combined first trimester screen would miss only a very small proportion of chromosomal anomalies, 31 whereas others indicate that up to 16.9% of aneuploidy would be missed, even when diagnostic testing is limited to G-banded karyotyping. 32 Studies that have utilised molecular karyotyping indicate that standard cfDNA testing alone would not identify up to 23.4% of potentially clinically significant karyotypic abnormalities that would otherwise have been identified by combined first trimester screening and invasive testing.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence from recent studies that the risk of miscarriage in women undergoing CVS may be lower than those that are currently stated. In a retrospective cohort study of 5148 women who had CVS compared with 4803 women who did not, the authors reported that there was no significant difference in the estimated fetal loss rate between the two groups (-0.67% (95% CI, -1.35 to 0.01%)) 39 . In another study, of 33 856 women including 2396 who underwent CVS, there was no significant difference in the risk of miscarriage after adjusting for maternal and pregnancy characteristics in women who had CVS compared with those who did not 40 .…”
Section: Studies On Chorionic Villus Samplingmentioning
confidence: 99%
“…In the CVS group, there were seven studies, comprising three observational retrospective cohort studies without a control group 9,36,37 , one observational retrospective cohort study with a control group matched for gestational age 39 , another similar cohort study with unmatched controls 38 , one control group that was derived from a 11-year national-registry database 30 and another study that was a prospective observational study for adverse pregnancy outcomes in which the controls were unselected women who had routine screening during the same period 40 . In four out of seven studies 9,30,39,40 CVS was performed in the first trimester, but there were three studies in which the procedure was carried out in the second or third trimester 36 -38 . In three out of four studies with a control group 38 -40 there was a defined starting point, all women in the control group being documented as having a viable fetus confirmed on ultrasound scan. This was, however, not the case with the national-registry based study 30 , for which it was not possible to confirm that in all pregnancies that did not have an invasive procedure, there was a viable fetus at the gestational age at which the invasive procedure was carried out ( Table 2).…”
Section: Characteristics Of Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…Thus, in 2008, the Washington University group in St. Louis published similar results, based on their experience of 11 746 amniocentesis and 5243 CVS procedures. They concluded that the 0.13% fetal-loss rate attributable to amniocentesis and the 0.7% attributable to CVS were not significantly different from those observed in pregnant women with no procedure 20,21 .…”
Section: Fetal Invasiveness: Decline Of the 1% Fetal-loss Rate Dogmamentioning
confidence: 92%